Optimasi Diplomasi Digital Sektor Pariwisata bagi Wisatawan Mancanegara di Kalimantan Barat - Nugrahaningsih, Nurfitri; Olifiani, Laras Putri (Intermestic: Journal of International Studies, 2023)
The use of digital technology is important and requires immediate attention, particularly in supporting economic development, notably in the tourism industry in West Kalimantan. Several programs have been implemented as a type of tourism diplomacy, despite the continued existence of practical barriers. Together with other relevant organizations, the Department of Youth, Sports, and Tourism manages the integration of tourism sector services in West Kalimantan. According to Bjola and Holmes, digital agenda setting, presence expansion, and conversation generation are three significant criteria for evaluating the efficacy and impact of employing digital media in public diplomacy efforts. Using a qualitative exploratory methodology, the authors intend to investigate and describe the digital diplomacy optimization for the tourism industry in West Kalimantan. According to the findings of this study, the diplomacy optimizatiol in West Kalimantan incorporates digital media as a platform for information dissemination, cooperation between diplomatic actors, and interaction between diplomatic actors and diplomatic targets.